2013
DOI: 10.1142/s2010495213500061
|View full text |Cite
|
Sign up to set email alerts
|

Partial Immunization Bounds and Non-Parallel Term Structure Shifts

Abstract: A variety of approaches have been proposed to extend classical fixed income portfolio immunization theory to cases where shifts in the term structure are not parallel. Following Reitano (1991a, 1991b, 1992, 1996) and Poitras (2007), this paper uses partial durations and convexities to specify benchmark partial immunization bounds for non-parallel term structure shifts. Theoretical results are obtained by exploiting properties of the multivariate Taylor series expansion of the spot interest rate pricing functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The classical fixed income interest rate immunization model uses a univariate Taylor series expansion to derive two rules for immunizing a zero surplus fixed income portfolio against a change in the level of interest rates: 1) match the duration of cash inflows (assets) and outflows (liabilities); and, 2) set the asset cash flows to have more dispersion (convexity) than the liability cash flows around that duration, e.g., Redington (1952), Shiu (1987Shiu ( , 1990, Reitano (1991aReitano ( , 1991bReitano ( , 1992Reitano ( , 1996, and Poitras (2007and Poitras ( , 2013. 8 In the classical case of a fixed income portfolio associated with a life insurance or pension company, surplus immunization is structured around the balance sheet of an individual fund.…”
Section: Basics Of Systemic Interest Rate Risk Immunizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical fixed income interest rate immunization model uses a univariate Taylor series expansion to derive two rules for immunizing a zero surplus fixed income portfolio against a change in the level of interest rates: 1) match the duration of cash inflows (assets) and outflows (liabilities); and, 2) set the asset cash flows to have more dispersion (convexity) than the liability cash flows around that duration, e.g., Redington (1952), Shiu (1987Shiu ( , 1990, Reitano (1991aReitano ( , 1991bReitano ( , 1992Reitano ( , 1996, and Poitras (2007and Poitras ( , 2013. 8 In the classical case of a fixed income portfolio associated with a life insurance or pension company, surplus immunization is structured around the balance sheet of an individual fund.…”
Section: Basics Of Systemic Interest Rate Risk Immunizationmentioning
confidence: 99%
“…The classical fixed income portfolio immunization model is extended to assess the implications of systemic interest rate and house price risk, e.g., Redington (1952), Reitano (1991a,b), and Poitras (2007and Poitras ( , 2013. It is demonstrated that shortening mortgage term to maturity and having a 'yield maintenance' prepayment penalty reduces the systemic risk inherent in the origination of long amortization period, single-family residential mortgages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation